Regulation of hypoxia‐inducible factor‐α isoforms and redox state by carotid body neural activity in rats. (28th July 2014) - Peng, Ying‐Jie; Yuan, Guoxiang; Khan, Shakil; Nanduri, Jayasri; Makarenko, Vladislav V.; Reddy, Vaddi Damodara; Vasavda, Chirag; Kumar, Ganesh K.; Semenza, Gregg L.; Prabhakar, Nanduri R.
Abstract : Key points: Rats exposed to chronic intermittent hypoxia (CIH) exhibited imbalanced expression of hypoxia‐inducible factor (HIF)‐α isoforms and oxidative stress in brainstem regions associated with the carotid body (CB) chemoreflex, and in the adrenal medulla, an end organ of the sympathetic nervous system. Selective ablation of the CB abolished the effects of CIH on HIF‐α isoform expression and oxidative stress. In the adrenal medulla, chemoreflex‐mediated sympathetic activation regulates HIF‐α isoform expression via muscarinic acetylcholine receptor‐mediated Ca 2+ influx and the resultant activation of the mammalian target of rapamycin pathway and calpain proteases. Thus, CB neural activity regulates HIF‐α isoform expressions and redox state in the central and peripheral nervous system associated with the chemoreflex pathway under the setting of CIH. Abstract: Previous studies reported that chronic intermittent hypoxia (CIH) results in an imbalanced expression of hypoxia‐inducible factor‐α (HIF‐α) isoforms and oxidative stress in rodents, which may be due either to the direct effect of CIH or indirectly via hitherto uncharacterized mechanism(s). As neural activity is a potent regulator of gene transcription, we hypothesized that carotid body (CB) neural activity contributes to CIH‐induced HIF‐α isoform expression and oxidative stress in the chemoreflex pathway. Experiments were performed on adult rats exposed to CIH for 10 days. Rats exposed to CIH exhibited: increased HIF‐1α and decreased HIF‐2α expression; increased NADPH oxidase 2 and decreased superoxide dismutase 2 expression; and oxidative stress in the nucleus tractus solitarius and rostral ventrolateral medulla as well as in the adrenal medulla (AM), a major end organ of the sympathetic nervous system. Selective ablation of the CB abolished these effects. In the AM, sympathetic activation by the CB chemoreflex mediates CIH‐induced HIF‐α isoform imbalance via muscarinic acetylcholine receptor‐mediated Ca 2+ influx, and the resultant activation of mammalian target of rapamycin pathway and calpain proteases. Rats exposed to CIH presented with hypertension, elevated sympathetic activity and increased circulating catecholamines. Selective ablation of either the CB (afferent pathway) or sympathetic innervation to the AM (efferent pathway) abolished these effects. These observations uncover CB neural activity‐dependent regulation of HIF‐α isoforms and the redox state by CIH in the central and peripheral nervous systems associated with the chemoreflex.